Karakteristik Wilayah Sebagai Basis Pendelegasian Kewenangan Kecamatan; Studi Kasus Di Kabupaten Sumbawa - Zulpikar, Zulpikar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
The management reforms of regional governance in Indonesia had started since the enactment of Law Number 22 Year 1999 regarding Regional Governance. The policy has influenced and changed the institutionalization/institution of between Central and Regional Government. Meanwhile, the implications that appeared towards the institutionalization of the regional government, amongst others, were the occurrence of less harmonious work relations between provincial and regency/city governments. Another implication that was also very important to be further observed was the institution of District that has become one of regional apparatus organizations since the implementation of Law. District seems have no important roles and functions like they had before. The main cause of this condition was about delegation of authority. Therefore, this descriptive case study was conducted. The main purpose of study was to find out the formulation of authorities that could be delegated. Case study was conducted in the Regency Government of Sumbawa where the districts were Sumbawa, Tarano and Lapelopok district. The basic concept used to build the formula of delegation of authorities was the potency of geographical characteristics. Primary data were collected through open and closed questions, whereas the secondary ones were collected from some relevant documents. Data were analyzed by triangulation method and statistical descriptive. The paper suggested that delegation of authorities should give differently based on geographical characteristics. Therefore, every district might have different authorities depend on their potencies